Yorùbá Proverbial Metaphor: A Rhetoric tool and Guiding Principle to Conflict Resolution - Emmanuel Oluniyi Ademola (Yoruba Studies Review)
The Yorùbá are a set of unique ethnic group with peculiar traditions, values and culture. Their cultural practice, heritage is found on the epitome of their proverbial prowess which are formed within the context of their traditional “Yorùbá language and dialect,” and used as a tool for conflict management and resolution. Conflict by Yorùbá belief is inevitable, but not insurmountable as Yorùbá found conflict always positive. To amplify this belief, Yorùbá at different occasions incorporate some of the proverbs that are relevant and applicable to conflicting situations in their attempt to resolve conflicts. This essay examines some of the selected proverbs while synthesized them as a rhetoric tools and guiding principles to constructive conflict resolution in the Yorùbá traditional Society. Suggestions are raised that application of proverbial maxims with Yorùbá perception on conflict and conflict resolution could be useful for peaceful handling of contemporary conflicts that are rampaging the African nations.